The Vulnerability of E-Commerce As A Crime Means of Money Laundering - Danang Tri Hartono; Dominikus Rato; Bayu Dwi Anggono (Green Publisher Indonesia, 2024)
Technological advances in the field of the internet and its supporting ecosystem have changed human lives. The way humans communicate, transact, trade and play games has changed massively. Along with the progress of the internet ecosystem, it has led to the emergence of trading platforms, both webservices and smartphone applications. Developments that change how people trade and pay for trade transactions cause vulnerabilities that can be used by criminals or to commit criminal acts. Criminal acts of fraud, unauthorized use of personal data, bribery through e-commerce media, and money laundering are criminal acts that have emerged along with the rampant use of e-commerce. Various methods of money laundering can be done using e-commerce media. One of the mitigations that can be done by the Government is to classify e-commerce media as a Reporting Party in the anti-money laundering regime.